The Person of Suspect in Criminal Procedure: Legal Historical Aspect - E. I. Zemlyanitsin (Сибирское юридическое обозрение, 2013)
The article deals with the historical path of the emergence and development of the legal rules governing the procedural status of a suspect in the criminal procedure. The author puts forward the proposal to amend the Criminal Procedure Code of the Russian Federation.